INVESTASI ASING DAN FUNGSI HUKUM DALAM MENARIK MODAL ASING UNTUK PEMBANGUNAN EKONOMI - Abdul Haris Afianto; Bhim Prakoso (Jurnal Cakrawala Ilmiah, 2023)
Foreign investment plays a crucial role in the economic development of a country. To attract foreign capital, the function of law is essential. This abstract will discuss the relationship between foreign investment and the role of law in the context of attracting foreign capital for economic development. Foreign investment can significantly contribute to the economic development of a country, such as increased production, job creation, technology transfer, and improved access to global markets. However, to attract foreign capital, a country must have a stable, transparent, and reliable legal environment. The role of law in attracting foreign investment encompasses several aspects. Firstly, clear and guaranteed investment laws provide legal certainty for foreign investors. This includes protection of property rights, protection against expropriation without fair compensation, and effective dispute resolution mechanisms. Secondly, fair and balanced labor laws provide certainty for investors regarding labor relations with local workers. Protection of workers' rights, freedom of association, and fair labor dispute resolution mechanisms are crucial factors in attracting foreign capital. Thirdly, clear and transparent tax laws provide certainty for investors regarding tax obligations and available fiscal incentives. An efficient and fair tax system can encourage foreign investment. Fourthly, stringent and sustainable environmental laws provide assurance that foreign investments will operate with consideration for the environment. Strong environmental protection and strict enforcement of environmental regulations can enhance investor confidence in the sustainability of their investments. In the context of attracting foreign capital for economic development, a strong and effective legal framework is crucial. A country must have a clear, transparent, and reliable legal environment to create an attractive investment climate for foreign investors. Thus, foreign investment can become a driver of sustainable economic growth and provide benefits for both the host country and foreign investors